Global Financial Crisis: Causes and Lessons. A Neo-Schumpeterian Perspective - Horst Hanusch; Florian Wackermann (Universität Augsburg, Institut für Volkswirtschaftslehre, 2009)
This paper analyses the current financial crisis from a Neo-Schumpeterian perspective. We postulate four linkages that led to the crisis, and that will help us find our way out of the crisis. Therefore, we show that the current evolution is very similar to the Japanese crisis in the beginning of the 1990s. Furthermore, we address the issue why the world was faced with this crisis in such an unprepared way and look at the deficiencies in current economic theories that are responsible for the fact that we did not foresee this development. Besides, we elaborate that the crisis is not a systemic default of the capitalistic system but that it is rather a consequence of its enormous success. Finally, we propose the Neo-Schumpeterian Corridor as a theoretical framework that can help avoid such dramatic evolutions as the current crisis and look at possibilities to overcome this situation.
urn:nbn:de:bvb:384-opus4-711309
Keywords: B52; G01; H11; N20; O20; 330